‘Amar al otro como a sí mismo’, y un muy peculiar tipo de oraciones recíprocas - Bejarano, Teresa (THÉMATA. Revista de Filosofía, 2013)
‘Amar al otro como a sí mismo’, y un muy peculiar tipo de oraciones recíprocas